Prosthetic approaches for immediate implants in esthetic areas: Aliterature review and clinical cases - Anchieta, Rodolfo Bruniera [UNESP] (My University, 2012)
The placement of implants in fresh extraction sockets followed for provisionalization allows soft tissues preservation and alveolar ridge, however for this some requisites are necessary. This article describe the factors involved in immediate implants and the prosthetic approachs for this type of therapy. Addtionaly two clinicals case were presented showing diferents approachs for in prosthetic stage for maintenance the aesthetic aperance of soft tissues of the immediate implants.
Keywords: Dental implants; Immediate implants; Immediate loading; Implant supported prostesis